Digital Forensic Investigation Model Based On Malaysian Standards With Live Forensic Investigation Tool - Sundresan A/L Perumal (Universiti Sains Islam Malaysia, 2024)
The digital world has advanced beyond that was imaginable decades before due to the inventions and innovations brought forth through developments in the complex field of cybertronics. These digital technologies and solutions are now so welded into our lives that the loss or absence of it may possibly mean utter catastrophe to mankind. The computer distinguishes itself and provides a better advantage by presenting the ability to interact with the user via the keyboard and its processed output. The cyberspace with the limitless capabilities it holds made innumerable lives easier as well as more difficult with a dark side known as digital crime. Therefore, due to the growing sophistication of digital crime, the ultimate question raised by professionals and enforcement officers is “What is the most concrete and effective method to prosecute digital criminals?” To answer this question, computer forensic procedures and cyber law have been introduced and implemented. The digital forensics regulation in Malaysia is still in the initial stages not having concise methods and standardized procedures in cybercrime investigation, no attention is being paid over the fragile evidence as live forensic stage is missing in the current digital forensic standard operating procedure. No portable live forensic tool currently being used by digital forensic investigator in Malaysia at the crime scene. The objective of this research is to introduce a new digital forensic model which focuses on live forensic data acquisition stage in digital forensic standard operating procedure and also to develop a handy GUI oriented live forensic data acquisition tool. The methodology used in validating the model and the tool will be by the digital forensic expert user from Malaysia and India. With the existence of this digital forensic model and digital live forensic tool the Malaysian digital forensic investigators will be more productive in accessing the crime scene and also able to effectively acquire the live data and proceed into solving the case.